A finite element program for the static analysis of branched, thin shells of revolution under axisymmetric loading - Griffin, T B (Department of Civil Engineering, 2023)
A finite element computer program which uses the conical, frustrum element is presented for the Linear elastic, static analysis of variable thickness, branched, thin shells of revolution, composed of straight sections and subject to general, axisymmetric mechanical, 1,oading. The thin she1,1, theory and finite element theory forming the basis of the analysis are described, with particular attention being given to the closing of the she l, 1, at the axis of symmetry, and shell branching. Numerous problems embodying al,1, relevant features of the program are analysed, and their solutions are discussed. A user's manual, for the program is appended, and guidelines for the efficient use of the program are given.